Learning of Older Adults in Makerspaces - Yong Ju Jung; Hyewon Park; Ellen L. Rubenstein (Adult Education Research Conference, 2022)
To address inclusion and equity issues related to older adults in makerspaces, we examine the void in current discussions of the maker movement and its intersection with adult learning theories.
Keywords: Makerspaces; maker movement; older adults; transformative learning; positive aging